2007
DOI: 10.3742/opem.2007.7.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of analgesic and antiinflammatory activity of Ophiorrhiza nicobarica, an ethnomedicine from Nicobar Islands, India

Abstract: SUMMARYThis study reports the analgesic, anti-inflammatory and membrane-stabilizing property of alcoholic extract of Ophiorrhiza nicobarica (ON), a wild herb, used as an anti-infective ethnomedicine of Nicobarese and Shompen tribes of Great Nicobar Island, India. We for the first time investigated the analgesic and antiinflammatory potential of this herb in acute, subacute and chronic model of inflammation in Swiss albino mice and Wistar albino rats, along with sheep RBC-induced sensitivity and membrane stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In our previous studies, we reported the moderate anti-inflammatory [22] and antimicrobial [23] activities of this plant extract. However, the present phytochemical investigations of active extract revealed three fractions, of which fractions A yielded an antivirally weak triterpene ursolic acid, while the fraction B contain antivirally inactive β-sitosterol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we reported the moderate anti-inflammatory [22] and antimicrobial [23] activities of this plant extract. However, the present phytochemical investigations of active extract revealed three fractions, of which fractions A yielded an antivirally weak triterpene ursolic acid, while the fraction B contain antivirally inactive β-sitosterol.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, new drugs with novel mode of action are required for the management and prevention of HSV infections. Here, we report the isolation of an antiviral compound from Ophiorrhiza nicobarica (International plant index Id: 758538-1), a traditional herb used by the Shompen and Nicobarese tribes of the Nicobar Islands, India, against skin ailments [21], having antimicrobial and antiinflammatory activities [22,23] with significant anti-HSV-2 activity. Further, we have demonstrated the in vitro mode of action and therapeutic efficacy of the isolated compound in Balb/C mice vaginally infected with HSV-2.…”
Section: Introductionmentioning
confidence: 99%
“…The Western Ghats are known as one of the diversity centres of Ophiorrhiza species following the Western Himalayas, which comprise of about 22 distributed taxa for the species [10]. Some of them that can be found in Andaman and the Nicobar islands of India include O. infundibularis Balakr, O. mungos L, O. nicobarica Balakr, and O. trichocarpa BL [11]. Meanwhile, about 30-35 species are documented in the shady and moist-to-wet areas in Thailand's lowland and mountain forests both [3], whereas Peninsular Malaysia is home to 21 species [6].…”
Section: Distributionmentioning
confidence: 99%
“…The Rubiaceae family is known with its capability of producing bioactive metabolites such as iridoids, indole alkaloids, anthraquinones, terpenoids (i.e., diterpenes and triterpenes), flavonoids, and many other derivatives of phenolic compounds, which result in their respective significant pharmacological activities [46]. The phytochemical analyses done for several species of Ophiorrhiza (Rubiaceae) have revealed the positive presence of alkaloids, flavonoids, and triterpenes, specifically in O. radicans [10], O. mungos [5], O. liukiuensis [37], and O. nicobarica [11]. Furthermore, some of the important phytochemicals found in most Ophiorrhiza species include camptothecin and its derivatives, namely pumiloside, luteolin, harman, tetrahydroalastonine, bracteatine, blumeanine, strictosidinic acid, and lyalosidic acid [49].…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation